The desert date tree, hero of the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Even in the most arid conditions, the desert date has much to offer: fruit, wood, oil, leaves and flowers. It is a species which deserves attention from researchers. After the droughts of the nineteen-seventies and eighties, the Sahel : looked like...